'After the manner of the Irish schools': the influence of Irish national education in the British Empire. (April 2018) - Lougheed, Kevin
Abstract: The establishment of the Commissioners of National Education in 1831 provided Ireland with a non-denominational education system that was aimed at uniting the population. The development and implementation of a state-controlled system of education represents a shift in policy away from a disciplinary mechanism used to proselytise Irish children to that of a governmental technology directed at influencing the conduct of the population. This paper looks at the ideology that influenced Irish national education, how that was representative of a wider imperial ideology, and how the Irish system itself influenced the spread of that ideology. It briefly examines the rationale, structure and operation of the national system, showing the attempt to refocus social relations through encouraging cooperation in the establishment and management of schools. In this way the influence of national education went beyond the classroom to wider society. The influence of Irish education reforms are then examined in respect to those in England and in the Anglophone colonies, notably in Canada and Australia. The direct influence of the Irish system across the British Empire, including the textbooks published in Ireland, represents the development of a wider rationale aimed at changing the conduct of colonists and creating imperial citizens. The Irish national system therefore went far beyond a model for the structure of an educational system, but also encouraged the spread of an imperial ideology that legitimised and secured the governance of colonial authorities across the British Empire. Highlights: Examines the shift in social relations that resulted from the creation of Irish national education. Explores why developments in English education followed a different route. Examines the application of the Irish model to education systems in Canada and Australia. Shows how Irish textbooks attempted to shift identity in the empire.